Not Only in My Genes: The Effects of Peers' Genotype on Obesity - Giorgio Brunello; Anna Sanz-de-Galdeano; Anastasia Terskaya (Institute of Labor Economics (IZA), 2019)
We use data from three waves of Add Health to study the short- and long-run effects of high school peers' genetic predisposition to high BMI – measured by grade-mates' average BMI polygenic scores – on adolescent and adult obesity in the U.S. We find that, in the short-run, a one standard deviation increase in peers' average BMI polygenic scores raises the probability of obesity for females by 2.8 percentage points, about half the size of the effect induced by a one standard deviation increase in one's own polygenic score. No significant effect is found for males. In the long-run, however, the social-genetic effect fades away, while the effect of one's own genetic risk for BMI increases substantially. We suggest that mechanisms explaining the short-run effect for females include changes in nutrition habits and a distorted perception of body size.
Keywords: D62; I1; I12; 330; obesity; peer effect; BMI polygenic scores; Add Health